2022
DOI: 10.1029/2022ja030830
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Storms During the Space Age: Occurrence and Relation to Varying Solar Activity

Abstract: We study the occurrence of magnetic storms in space age (1957–2021) using Dst and Dxt indices. We find 2,526/2,743 magnetic storms in the Dxt/Dst index, out of which 45% are weak, 40% moderate, 12% intense and 3% major storms. Occurrence of storms in space age follows the slow decrease of sunspot activity and the related change in solar magnetic structure. We quantify the sunspot—coronal mass ejection (CME) storm relation in the five cycles of space age. We explain how the varying solar activity changes the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
(145 reference statements)
4
5
0
Order By: Relevance
“…The days of fast solar wind had local maxima at the declining phases of solar cycles 23-24, and local minima near the beginning of the inclining phases of cycles 23-25. This is consistent with previous observations showing that the highest solar wind speeds are observed during the declining solar cycle phase when coronal holes extend to lower solar latitudes (Gosling et al, 1976;Mursula et al, 2017Mursula et al, , 2022.…”
Section: Overview Over Three Solar Cyclessupporting
confidence: 93%
See 2 more Smart Citations
“…The days of fast solar wind had local maxima at the declining phases of solar cycles 23-24, and local minima near the beginning of the inclining phases of cycles 23-25. This is consistent with previous observations showing that the highest solar wind speeds are observed during the declining solar cycle phase when coronal holes extend to lower solar latitudes (Gosling et al, 1976;Mursula et al, 2017Mursula et al, , 2022.…”
Section: Overview Over Three Solar Cyclessupporting
confidence: 93%
“…This is consistent with the highest solar wind speeds occurring at the declining solar cycle phase (Gosling et al, 1976;Mursula et al, 2017Mursula et al, , 2022, as well as the formation of corotating interaction regions (CIRs), which together with coronal mass ejections (CMEs), are known to cause increased geomagnetic activity (Richardson et al, 2006;Zhang et al, 2007). Note that the peak in the occurrence of the high-speed solar wind has been observed to shift from the late to the earlier declining phase in solar cycles 23-24 (Mursula et al, 2022). This is consistent with our observations of the peak in the number of SUBs occurring somewhat earlier in the declining phase of cycle 23-24 as compared to cycle 22 (Figure 6d).…”
Section: Overview Over Three Solar Cyclessupporting
confidence: 86%
See 1 more Smart Citation
“…Borovsky and Denton (2006) also noted that both CIRs and the high-speed solar wind streams that typically follow them can be drivers of storms, and that when recurring CIR-driven storms were ongoing (which tends to be in the declining phase of the solar cycle), the durations of high-speed streams were longer. Mursula et al (2022) showed the importance of variations in the width of the heliospheric current sheet (HCS) for the relative occurrence of geomagnetic storms related to CMEs, HSS/CIRs, and slow solar wind, respectively, such that a wide HCS made large and moderate HSS/CIR storms occur in the early declining phase in recent cycles 23 and 24 (1996-2019), while in the more active cycles 20-22 (1964-1996) they occurred in the late declining phase (their Figure 5). Tsurutani et al (2006) reviewed the causes, characteristics, and consequences of CIRs and high-speed streams, in particular their association with auroral substorms.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of ≥ 20 nT/s GMD events as a function of geomagnetic storm phase.Definitions for the four storm categories are taken fromMursula et al (2022).…”
mentioning
confidence: 99%